2012
DOI: 10.1093/annhyg/mes009
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Ergonomic Devices on Mechanical Load during Patient Handling Activities in Nursing Homes

Abstract: In wards in nursing homes with a higher number of staff less awkward back postures as well as forceful lifting were observed during patient handling activities. The use of ergonomic devices was high and associated with less forceful movements and awkward back postures. Both aspects will most likely contribute to the prevention of low back pain among nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 40 publications
1
25
0
2
Order By: Relevance
“…Resistance to change is one; ergonomic device use can be variable, with nurses sometimes choosing not to use a device when it is recommended, or to the extent that it was intended. Reasons given include: poor access, insufficient training, lack of space for use or storage, inadequate staffing, or increased time required compared with manual methods [5,7,41,46]. Knibbe et al found the behaviour change required in nurses was a major issue with implementation of device use-to adjust from two or more persons to only one required an adjustment in attitude for the nurse to realise that this was still safe practice [47].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Resistance to change is one; ergonomic device use can be variable, with nurses sometimes choosing not to use a device when it is recommended, or to the extent that it was intended. Reasons given include: poor access, insufficient training, lack of space for use or storage, inadequate staffing, or increased time required compared with manual methods [5,7,41,46]. Knibbe et al found the behaviour change required in nurses was a major issue with implementation of device use-to adjust from two or more persons to only one required an adjustment in attitude for the nurse to realise that this was still safe practice [47].…”
Section: Discussionmentioning
confidence: 99%
“…The number of lost workdays due to injury was also generally reduced with introduction of ergonomic devices [7,43,45], as were costs associated with patient handling-related injury [45]. Use of ergonomic devices was also associated with reduced awkward back posture incidence and duration [46], safer patient transfers [47], and reduced risk of infrequent lower back pain [48]. Burdorf et al reported, however, that even the best scenario only showed a maximal reduction of 14% in lower back pain prevalence, while the projection from this analysis was that complete elimination of manual patient lifting would reduce lower back pain by 10.5% [43].…”
Section: In Relation To Healthcare Workers: Ergonomic Devices And/or mentioning
confidence: 99%
See 3 more Smart Citations